Hatchery's Assistant's Cottage - Jackson Benson:::Creator::::::::::::
A Color photo of Hatchery's assistant's cottage. An inscription on back of photo reads: 'Hatchery Assistant's cottage which John shared with (Lloyd) Shebley....'